Development of Mechanical Extractor for Utilization of Pineapple Leaf Agro-Waste for Textile Application - Laxmi Kanta Nayak; Nageshkumar T; Prateek Shrivastava; Manisha Jagadale; Haokhothang Baite; Vidya Bhushan Shambhu; Manjunatha B. S. (Journal of Natural Fibers)
In Indian subcontinent, pineapple (Ananas Comosus) leaves are left unused after fruits are harvested resulting in a waste of natural resources that contain textile-graded fibers. The present study intended to develop a pineapple leaf fiber extractor to chip off the waxy layer of the leaf. The machine comprised feeding conveyor, feed rollers, scratching roller, combing roller, frame and motor as a power source with a transmission unit. The performance was evaluated under different independent variables, i.e. rpm of the scratching roller (100, 150 and 200 rpm), types of secondary roller (combing, serration and without secondary roller) and moisture content of leaf (85 ± 3, 78 ± 3 and 71 ± 2%). Response surface method of optimization was employed to optimize the operational parameters. Best combination of operating parameters was found to be 150 rpm scratching rollers, combing type secondary rollers and moisture content of 85 ± 3%. It was found that the retting duration, processing efficiency, and fiber yield were 4 days, 88.9%, and 2.41% at optimized parameters, respectively. Further, throughput capacity and power requirement were found to be 33 ± 2 kg/hand 1.5 kWh respectively. The developed machine found to be effective in extracting waxy layer on leaves with minimal damage to useable fiber.